2008
DOI: 10.1590/s0100-06832008000700008
|View full text |Cite
|
Sign up to set email alerts
|

Mineralização do carbono da palha de aveia e dejetos de suínos aplicados na superfície ou incorporados ao solo

Abstract: RESUMOA mineralização do C de dejetos de suínos e de palhas de cereais é um processo ainda relativamente pouco estudado no Brasil. O objetivo deste trabalho foi avaliar a mineralização do C da palha de aveia, dos dejetos líquidos de suínos e da cama sobreposta de suínos, aplicados na superfície ou incorporados em um Argissolo Vermelho distrófico arênico, em condições de laboratório. Utilizou-se o delineamento inteiramente casualizado, com quatro repetições dos seguintes tratamentos: solo; solo + palha incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
1
14
0
3
Order By: Relevance
“…Whereas Giacomini et al (2008), did not observed higher C release in the form of CO 2 from oat straw with pig slurry and pig litter bedding, applied to a sandy Red Hapludalf soil.…”
Section: Resultsmentioning
confidence: 72%
“…Whereas Giacomini et al (2008), did not observed higher C release in the form of CO 2 from oat straw with pig slurry and pig litter bedding, applied to a sandy Red Hapludalf soil.…”
Section: Resultsmentioning
confidence: 72%
“…After containers had been aerated for 10 min on each sampling date, a new flask containing 1 mol L -1 NaOH solution was suspended within each glass container. Apparent C mineralization from SS and OS was calculated by subtracting the quantity of CO 2 -C emitted by the treatment containing only soil (S) by the quantity of CO 2 -C emitted by each treatment (SSi, OSi and SSi + OSi) as described by Giacomini et al (2008). Apparent N mineralization was calculated using the equation adopted by Giacomini et al (2013):…”
Section: Methodsmentioning
confidence: 99%
“…In general, organic waste has high levels of macronutrients such as N, P, K, Ca (Aita et al, 2007;Giacomini et al, 2009), and micronutrients such as B, Zn and Mn. Since the application of organic waste can change biological and biochemical indicators, studies are needed to measure the effect of this practice on soil (Martens, 2000;Ros et al, 2003;Tejada et al, 2006).…”
Section: Introductionmentioning
confidence: 99%